A Review Of The Analysis Of Amphibole Fibers - D. R. Van Orden; R. J. Lee; K. A. Allison (Society for Mining, Metallurgy & Exploration, 2005)
Continuing analysis of environmental samples for asbestos content has resulted in the misidentification of non-asbestos amphibole particles as asbestos fibers. These errors have received wide publicity (such as in the asbestos-in-crayon story) and have caused unnecessary reformulation of products. The primary cause of these errors has been a poor understanding of mineralogy and analytical techniques among the many asbestos laboratories that arose following the passage of the AHERA regulations. Presented here is a procedure based on published data that can be used to correctly classify an elongated particle as asbestos or as non-asbestos.